SIGNIFICANCE OF JAIN PHILOSOPHY FOR PRESERVING LIFE AND ENVIRONMENT - Sekhar, Vincent (Journal of Dharma, 2001)
A few years ago, a question was put to a few Jain scholars across the country: what sort of society does Jainism want to project? The answer was more or less unanimous: a non-violent society! They went on to add that their religion preached ahimsa, non-violence, more than any other thing and non-violence was the need of the hour to protect life and environment. A proper understanding of the principle of ahimsa and its honest practice by humans can immensely ameliorate the health of environment. The eco-spirituality and ecosophy of Jainism ultimately consist in upholding this principle and realizing it in life. Ahimsa, for Jains, is not just a social virtue and a religious rule; it is the very criterion and norm of spirituality and religiosity.